RELATIONSHIP BETWEEN PARITY AND FAMILY SUPPORT WITH REGULARITY OF CONSUMPTION OF BLOOD ENHANCER TABLETS IN PREGNANT WOMEN - Yasrida Nadeak; Ratih Sri Rahmadani; Polma Ria Panjaitan; Ika Damayanti Sipayung (Getsempena Health Science Journal, 2025)
Anemia in pregnancy is a public health problem that is still highly prevalent in Indonesia and has serious impacts on maternal health and fetal development. The impact of anemia during pregnancy is not only short-term but also long-term, both for the mother and the fetus. One of the recommended preventive efforts is regular consumption of iron tablets (TTD) during pregnancy. However, the level of compliance of pregnant women in consuming TTD is still relatively low. This study aims to analyze the relationship between parity and family support with the regularity of TTD consumption in pregnant women in Muara Batu-Batu Village, Rundeng District. The study used a quantitative approach with a cross-sectional design. A total of 52 respondents were selected using purposive sampling techniques based on inclusion criteria, namely pregnant women who had received TTD from health workers, did not experience pregnancy complications, and were willing to be respondents. Data collection was carried out using questionnaires and documentation, then analyzed using the chi-square test. The results showed that the majority of respondents were grandemultipara (88.5%), unemployed (88.4%), and had hemoglobin levels <11.5 gr% (65.1%). As many as 59.6% of respondents were recorded as irregular in consuming TTD. Statistical tests showed a significant relationship between family support and regularity of TTD consumption (p = 0.003), while no significant relationship was found between parity and regularity of TTD consumption (p = 0.610). This finding confirms that family support, whether in the form of emotional motivation, information, or practical assistance, is a determining factor in increasing compliance of pregnant women. In contrast, the number of previous pregnancies did not have a direct effect. Therefore, increasing education and family involvement needs to be strengthened in maternal health interventions, especially iron supplementation programs.